سياسة بنك الجزائر في مواجهة التسرب النقدي وأثره على سيولة المصارف دراسة حالة 2001 / 2022 - بثينة دعاس; رشا بن عمارة (My University, 2022)
Our study aims to know the extent of the contribution of Summary:the Bank of Algeria's policy in the face of cash leakage, through the use of a set of qualitative and quantitative tools of monetary policy, to achieve its goals and objectives. Monitoring liquidity and administrative work. This study dealt with the issue of monetary reforms initiated by the state since 2001. As for the practical side, it dealt with the phenomenon of cash leakage and its impact on the volume of trade exchange between commercial banks through an applied study on. Cash disbursement using the quantitative statistical method to test hypotheses and analyze data and data. The study concluded that there is an effect of money supply leakage on monetary circulation. ....................................................... /